Clinical Studies Concerning Factor XIII; with Special Reference to Hyperlipemia - Cucuianu, Mircea P.; Vasile, Vasile V.; Popescu, Titus A.; Opincaru, Augustin; Crîsnic, Ion; Tapalagå, Daniela (Thrombosis and Haemostasis, 1973)
Factor XIII, estimated according to the method of Heene, was found to be diminished in patients with cirrhosis of the liver, in acute renal failure and, to a lesser extent, postoperatively, owing probably to both a decreased synthesis and an accelerated utilization. When compared to values obtained in healthy, normal weight, normolipemic control subjects, the level of factor XIII was higher in hyperlipemic and especially in hypertriglyceridemic patients, whether clinical atherosclerosis was present or not. Low levels of factor XIII were usually accompanied by a decrease in serum pseudocholinesterase, while high values of this enzyme produced by the liver were noted in hypertriglyceridemic patients. The hypothesis of an enhanced synthesis of factor XIII by the liver, in subjects with endogenous hypertriglyceridemia is considered. It is also suggested that accelerated stabilization of fibrin might contribute to the fibrinolytic insufficiency of hyperlipemic patients and enhance certain atherogenic mechanisms.